Abordagem metodológica para o ensino de trigonometria por meio de material manipulável e registros de representação semiótica - Pagliarini, Marciano Mauro (2016)
With the intention to demystify the study about Trigonometry, it proposes to the bibliographic study of the appearance of the people who gave their contributions allowing to develop over the times. We also discuss here some ways to demonstrate trigonometric functions in different representations. In this sense is enhanced the theory of Raymond Duval, on semiotics registers representation, which became evident in the last two decades . Such fact is described an evidence that it is only possible the learning of mathematical object , when the student can visualize the process using different forms of representations. To facilitate the transit of a mathematical object , we have opted for the construction of a manipulable material. Both the students and teachers started to make calculations and demonstrate the different ratios between geometric shapes and trigonometric that were only known to some as algebraically. In order to get the teacher´s opinion about the use of manipulable material to make easy the information about mathematical object, a workshop was developed . It has shown that they can see different functions in different ways and were assisted in the construction and instruction of this manipulable material. With the data collected from this workshop participants , the researcher decided to test the effectiveness of this methodology , applying a similar workshop to the students of the second year of high school, getting good results.